2014
DOI: 10.1016/j.bbrc.2014.03.138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a genetic interaction between the tumor suppressor EAF2 and the retinoblastoma protein (Rb) signaling pathway in C. elegans and prostate cancer cells

Abstract: The tumor suppressor EAF2 is regulated by androgen signaling and associated with prostate cancer. While EAF2 and its partner ELL have been shown to be members of protein complexes involved in RNA polymerase II transcriptional elongation, the biologic roles for EAF2 especially with regards to the development of cancer remains poorly understood. We have previously identified the eaf-1 gene in C. elegans as the ortholog of EAF2, and shown that eaf-1 interacts with the ELL ortholog ell-1 to control development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In this study we performed a systematic approach to identify bilaterian-438 specific genes. Previous investigations concluded that essentially all impor-439 tant developmental regulators precede the origin of bilaterians, and that 440 rewiring of already existing factors was a hallmark of bilaterian evolution 441 [24,56,23,22,48] and our results enhanced by a second BLAST and phy-442 logeny based control step are in support of this. Future data from non-443 bilaterian species might in fact show that even the 35 groups of orthologues 444 we now identified to be conserved across the three model species but with-445 out credible non-bilaterian orthologues were present before the split from…”
supporting
confidence: 74%
“…In this study we performed a systematic approach to identify bilaterian-438 specific genes. Previous investigations concluded that essentially all impor-439 tant developmental regulators precede the origin of bilaterians, and that 440 rewiring of already existing factors was a hallmark of bilaterian evolution 441 [24,56,23,22,48] and our results enhanced by a second BLAST and phy-442 logeny based control step are in support of this. Future data from non-443 bilaterian species might in fact show that even the 35 groups of orthologues 444 we now identified to be conserved across the three model species but with-445 out credible non-bilaterian orthologues were present before the split from…”
supporting
confidence: 74%
“…EAF2 was also shown to act as a tumor suppressor in the murine prostate [17] . More recently, we identified genetic interactions between the EAF2 ortholog in C. elegan s and the retinoblastoma protein (RB) signaling pathway [20] . Thus, ELL2 may also suppress prostate cancer and interact with RB signaling.…”
Section: Introductionmentioning
confidence: 99%
“…2 :: GFP; rol-6 (su1006)] ) [ 54 ], DA2123 ( adIs2122 [lgg-1p :: GFP :: lgg-1 + rol-6(su1006)] ) [ 110 ], HZ1688 ( atg-13(bp414) ) [ 88 ], MAH236 ( sqIs13 [lgg-1p :: GFP :: lgg-1 + odr-1p :: RFP] ) [ 86 ], SJ4001 ( zcIs1[aip-1 :: GFP] ) [ 37 ], and VC1369 ( rpn-10(ok1865) ) were obtained from the Caenorhabditis Genetics Center which is funded by NIH Office of Research Infrastructure Programs (P40 OD010440). The rrIs1[elt-2 :: lacZ :: GFP] transgene which expresses nuclear localized GFP in the intestine has been previously described [ 111 ]. The rpn-10(ok1865) mutant was outcrossed against N2 five times, and one resulting outcrossed homozygous line was used for all subsequent crosses and experiments.…”
Section: Methodsmentioning
confidence: 99%